Analysis of Factors Affecting Profit Growth of Sharia Commercial Banks in Indonesia Period 2014-2023 - Muhammad Fakhrul Al-Rasyid; Yaser Taufik Syamlan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study explores the factors influencing profit growth in Islamic commercial banks in Indonesia, focusing on Return on Assets (ROA) as the dependent variable. The independent variables analyzed include one-month deposits, Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF) Murabahah, Financing to Deposit Ratio (FDR), Operational Costs to Operational Income (BOPO), and Mismatch. Secondary data from the Sharia Banking Statistics (SPS) of the Financial Services Authority (OJK) for 2014–2023 is utilized. Using the Vector Error Correction Model (VECM), findings indicate that CAR negatively affects ROA in the long term, while NPF Murabahah has a significant positive impact. However, one-month deposits, FDR, BOPO, and Mismatch do not exhibit a significant long-term effect. In the short run, ROA is primarily influenced by its past values, with no notable impact from other variables. The impulse response function analysis shows that ROA reacts positively to shocks in NPF Murabahah and Mismatch, stabilizing over time, while negative responses are observed for shocks in 1-month deposits, CAR, FDR, and BOPO. Variance Decomposition Analysis further reveals that, apart from ROA itself, Mismatch contributes the most to ROA fluctuations, whereas BOPO has the least effect.